Sequence analysis and acoustic tracking of individual lake sturgeon identify multiple patterns of river–lake habitat use. Issue 12 (9th December 2019) - Colborne, Scott F.; Hondorp, Darryl W.; Holbrook, Christopher M.; Lowe, Michael R.; Boase, James C.; Chiotti, Justin A.; Wills, Todd C.; Roseman, Edward F.; Krueger, Charles C.
Abstract: Understanding the spatial ecology of sturgeon (Acipenseridae) has proven to be a challenge due to the life history characteristics of these fish, especially their long life span, intermittent spawning, and long‐distance migrations. Within the Huron‐Erie Corridor (HEC) of the Laurentian Great Lakes, habitat use of 247 lake sturgeon ( Acipenser fulvescens ) was monitored over a three‐year period (2015–2017) with acoustic transmitters. Extensive spatial coverage of receivers throughout the St. Clair River, Lake St. Clair, and Detroit River between Lake Huron and Lake Erie (~150 km) allowed for continuous monitoring of the movements of acoustic‐tagged individuals. Sequence analysis of individual detection histories was used to describe lake sturgeon habitat use and to determine (1) whether distinct habitat‐use patterns occurred within the HEC; (2) whether the range of habitats occupied varied across seasons among sturgeon grouped by common patterns; and (3) whether variation identified was related to tagging sites in the two rivers or sex. Lake sturgeon were active throughout the HEC, but five distinct habitat‐use patterns were identified. River residents were not broadly distributed across entire rivers, but rather associated with particular segments (middle Detroit River, St. Clair River delta). Variations in habitat‐use sequences were in part related to three river tagging sites, but not sex, and did not produce groups with sequences that reflected all five habitat‐use patterns derived from cluster analysis. Lake sturgeon distribution was reduced to fewer habitat segments during winter and expanded to the maximum extent during the spring and summer. Conservation planning that incorporates behavioral diversity of habitat use is relatively rare due to a lack of observations on movements of individuals at biologically relevant spatial and temporal scales, but using telemetry and sequence analysis methods may promote the success of conservation and restoration efforts.